O orçamento municipal de saúde: um estudo de caso, Conceição do Araguaia – PA - SANTOS, Hiana Oliveira dos (2023)
This work has for objective to analyze the budget of the health in the City of Concision of the Araguaia, being explicated the job of the Systems of Information; to reach this intention, an empiricist-analytical methodological boarding with the conduction of a Study of Case of the management of the politics of municipal health was chosen; one proved the historical concept, aspects, the composition, the legislation, focalization, the principles and the classification of the public budget of health, specifying the distribution of resources between the government spheres; the antecedents, principles and norms had been discriminated that conduct the Only System of Health (SUS); they had been presented given and to information concerning the city reference, enclosing its religious, cultural and physicist-territorial description, aspects, statistical data of economic and social order, as well as the pertinent ones to the research of field carried through together to the City department of Health; it was concluded that the job of the Systems of Information, in special of the SIOPS, assists in the process of decision taking, constitutes estimated to guarantee the view of mounts of money and the framing of the City to the requirements of management of the Health department.